Financiamento público da educação a distância nas universidades federais brasileiras - Medeiros, Fernandina Fernandes de Lima (2025)
Distance Education has taken on an increasingly important role in expanding access to public higher education in Brazil, particularly within the scope of federal universities. This thesis aimed to analyze the funding mechanisms adopted by the Brazilian government for the implementation and development of Distance Education programs in Federal Institutions of Higher Education, identifying elements that may contribute to the formulation of improved public policies in this field. A methodological triangulation approach was used, combining both qualitative and quantitative methods. The research included a systematic literature review, analysis of institutional documents, a virtual questionnaire conducted between March 16 and April 16, 2025, and semi-structured interviews with professionals working in the field, carried out between April 17 and 22, 2025. The empirical analysis was organized around four main areas: funding, institutionalization, quality, and the role of the Open University of Brazil. The results indicate that the absence of a continuous funding model undermines the planning and integration of Distance Education into the academic and administrative structures of federal universities. The study also found that the responsible teams and learning centers (polos) face frequent instability in maintaining regular operations, which hinders the consolidation of the modality. Despite these challenges, Distance Education continues to play an essential role by reaching students in regions historically excluded from face-to-face higher education. The analysis showed that although the modality is present in institutions, its continuity still depends on provisional arrangements and temporary decisions. In response, this thesis proposes concrete measures, such as the creation of a dedicated budget line, formalization of tutor roles, and the strengthening of public control over educational technologies. It concludes that the advancement of Distance Education in federal universities requires budget predictability, stable institutional structures, and its inclusion in formal academic governance. More than regulatory frameworks, the lasting presence of Distance Education as part of the public university system depends on political decisions aligned with education as a foundation for social transformation.